Evaluating REBT Group Counseling with Journaling Techniques for Improving Self-Compassion in Javanese Students - Resa Pujianti; Eni Rindi Antika; Eem Munawaroh (Pamomong: Journal of Islamic Educational Counseling, 2025)
Adolescents often labeled as the “strawberry generation” tend to show low self-acceptance and harsh self-criticism, conditions that are closely related to low self-compassion. This study examined the effectiveness of REBT-based group counseling with journaling in enhancing adolescents’ self-compassion. A quantitative quasi-experimental design was employed using a pretest–posttest non-equivalent control group. Participants were 10 tenth- and eleventh-grade students from a senior high school in Central Java, selected through purposive sampling and assigned to an experimental group (N = 5) and a control group (N = 5). Self-compassion was measured using a self-report scale administered before and after the intervention. Data were analyzed using an independent samples t-test. The results showed a significance value of .013 (p < .05), indicating a significant difference in gain scores between the experimental and control groups. The experimental group obtained a mean gain score of 18.4, whereas the control group obtained −1.0, demonstrating that REBT-based group counseling with journaling is effective in improving adolescents’ self-compassion. This study is limited by its small sample size, brief intervention period, and restricted monitoring of changes outside counseling sessions, which may affect the generalizability and stability of the findings. Future research should involve larger samples, longer interventions, and more varied monitoring tools to further optimize and evaluate journaling-based group counseling for adolescent self-compassion.